Improving schools through school choice : An experimental study of deferred acceptance - Klijn, Flip (2022)
In the context of school choice, we experimentally study the student-optimal stable mechanism where subjects take the role of students and schools are passive. Specifically, we study if a school can be better off when it unambiguously improves in the students’ true preferences and its (theoretic) student-optimal stable match remains the same or gets worse. Using first-order stochastic dominance to evaluate the schools’ distributions over their actual matches, we find that schools’ welfare almost always changes in the same direction as the change of the student-optimal stable matching, i.e., incentives to improve school quality are nearly idle.